2011
DOI: 10.1107/s1600536811039110
|View full text |Cite
|
Sign up to set email alerts
|

(2E)-1-(Pyridin-2-yl)-3-(2,4,6-trimethoxyphenyl)prop-2-en-1-one

Abstract: The title heteroaryl chalcone derivative, C17H17NO4, is a condensation product of 2-acetyl­pyridine and 2,4,6-trimeth­oxy­benzaldehyde. The mol­ecule is roughly planar, the dihedral angle between the pyridine and benzene rings being 5.51 (10)°. All the three meth­oxy groups are almost co-planar with the bound benzene ring [r.m.s. deviation of 0.0306 (2) Å]. A weak C—H⋯O intra­molecular inter­action involving one of the ortho-meth­oxy groups generates an S(6) ring motif. In the crystal, the mol­ecules are linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In each molecule, intramolecular C-H•••O weak interaction (Table 1) generates S(6) ring motif (Bernstein et al, 1995). The bond distances agree with the literature values (Allen et al, 1987) and are comparable with those observed in related structures (Chantrapromma et al, 2009;Fun et al, 2010Fun et al, , 2011Suwunwong et al, 2009).…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…In each molecule, intramolecular C-H•••O weak interaction (Table 1) generates S(6) ring motif (Bernstein et al, 1995). The bond distances agree with the literature values (Allen et al, 1987) and are comparable with those observed in related structures (Chantrapromma et al, 2009;Fun et al, 2010Fun et al, , 2011Suwunwong et al, 2009).…”
Section: Methodssupporting
confidence: 87%
“…For related literature on hydrogen-bond motifs, see: Bernstein et al (1995). For related structures, see: Chantrapromma et al (2009); Fun et al (2010Fun et al ( , 2011; Suwunwong et al (2009). For background to and applications of chalcones, see: Go et al (2005); Liu et al (2008); Ng et al (2009); Ni et al (2004); Suwunwong et al (2011); Tewtrakul et al (2003).…”
Section: Related Literaturementioning
confidence: 99%
“…At the same time, the CSD revealed the existence of some examples of structurally similar vinyl ketones, viz. 1-(4chlorophenyl)-3-(2,4,5-trimethoxyphenyl)prop-2-en-1-one (Teh et al, 2006), (2E)-1-(pyridin-2-yl)-3-(2,4,6-trimethoxyphenyl)prop-2-en-1-one (Fun et al, 2011), (2E)-1-(pyridin-2yl)-3-(2,4,5-trimethoxyphenyl)prop-2-en-1-one (Chantrapromma et al, 2013) and (1E,4Z,6E)-5-hydroxy-1,7-bis(2methoxyphenyl)-1,4,6-heptatrien-3-one (Zhao et al, 2011).…”
Section: Database Surveymentioning
confidence: 99%